Mapeamento de epitopos funcionais do receptor CD14 por Phage Display e o reconhecimento de componentes bacterianos - Alves, Patrícia Terra (2013)
The cluster of differentiation antigen 14 (CD14) is a key molecule of the innate immunity. This pattern recognition receptor binds mainly to lipopolysaccharide (LPS), lipotechoic acid, arachidonic acid and thus induces the releases various cytokines as a defense mechanism. Several studies suggest that different regions of the amino-terminal portion of the molecule may be involved in the LPS binding; however, controversial results on the recognition sequence still persist. In this work, functional epitopes of the CD14 molecule were mapped through Phage Display by using a 7-mer conformational constrained random peptide library against a monoclonal antibody anti-soluble CD14-fraction ST and a polyclonal anti-CD14. In silico and empirical analyzes were performed to map the selected peptides into the CD14 3D structure. Immunoreactivity tests of peptides against bacterial components of Gram+ and Gram- bacteria were performed in order to demonstrate their functional recognition. All peptides strongly reacted against all bacteria, and besides the recongtion of the amino-terminal region, we were able to demonstrate a second epitope site in the middle of the receptor. Additional in silico analysis suggests a possible role of CD14 epitopes as natural antimicrobial peptides.